Outcomes in ED patients with non‐specific ECG findings and low high‐sensitivity troponin. Issue 6 (17th November 2022) - Alshaikh, Lamees M.; Apple, Fred S.; Christenson, Robert H.; deFilippi, Christopher R.; Limkakeng, Alexander T.; McCord, James; Nowak, Richard M.; Singer, Adam J.; Peacock, W. Frank
Abstract: Background: Although some emergency department risk stratification tools consider non‐specific ECG findings as an aid in disposition decisions, their clinical value in patients with an initially low high‐sensitivity cardiac troponin I (hsTnI) is unclear. Objective: Our purpose was to determine if non‐specific ECG (ns‐ECG) findings are associated with 30‐day major adverse cardiac events (MACE) in ED patients presenting with suspected acute coronary syndromes (ACS) who have a low initial hsTnI. Methods: Using the prospective Siemens Atellica hsTnI Food and Drug Administration submission observational database, we conducted a retrospective cohort study of the association between ns‐ECG findings (defined as left bundle branch block [LBBB], ST depression [STD], or T‐wave inversions [TWI]) and 30‐day MACE (death, myocardial infarction, heart failure hospitalization, or coronary revascularization). Eligible patients presented with suspected ACS to one of 29 US EDs from April 2015 to April 2016, had stable vital signs, a blood sample for hsTnI (Siemen's Atellica, Siemens Healthineers, Inc, Malvern, PA) obtained at 1, 3, and 6 hours after ED presentation, and were followed for 30 days. The relationship between 30‐day outcome, initial hsTnI, and ns‐ECG was evaluated using chi‐square testing. Results: Of 2676 enrolled, 1313 patients met the inclusion criteria and are included in the analysis. Median (interquartile range) age was 62 years (54, 72), 54% were male, with 56% white, and 39% African American. Median (interquartile range) times from symptom onset to presentation and presentation to specimen collection were 92 (0, 216) and 146 (117, 177) minutes, respectively. The most common presenting symptoms were chest pain (84%), followed by dyspnea (9%). ECG findings were categorized as T‐wave inversion or non‐specific T wave changes (42%), ST depression ns‐ECG ST changes (16%), or LBBB (2%). Thirty‐day MACE occurred in 72 (5.5%) patients, with coronary revascularization (35 patients, 2.7%) and heart failure (25 patients, 1.9%) being the most frequent outcomes. In patients with an initial hsTnI below the limit of quantitation (LOQ) of 2.5 ng/L (n = 449), there was no association between ns‐ECG changes and 30‐day MACE ( P  = 0.42). If the hsTnI was ≥LOQ (2.5 ng/L), there were increased rates of 30‐day MACE and ns‐ECG findings ( P  = 0.01). Conclusion: In ED suspected ACS patients without unstable vital signs, and an initial hsTnI less than the LOQ (2.5 ng/L), ns‐ECG findings are not associated with 30‐day major adverse cardiac events. The use of ns‐ECG findings in ACS disposition should be considered in the context of hsTnI levels.